Assessing the effect of layering gingival shade composite resin thickness on the flexural strength of denture base polymer resin material processed by CAD/CAM and injection moulded technique - Vikas Punia; Vaishnavi Ghuge; Anand Porwal; Abhijit Sethia; Palak Salgia; Jehan Dordi; Apexa Tuvar (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Acrylic resin denture base as materials for dentures, do not mimic the gingival esthetics. Gingival composite resin used for fabrication of denture; it enhances the denture esthetics but affects the material's flexural strength. The study aimed to investigate the flexural strength of denture base polymer resin material CAD/CAM milling and injection molding, as well as the impact of gingival shade composite resin thickness. Methods: Two types of denture acrylic resins were used as base materials: CAD/CAM pre-polymerized PMMA resin and injection molded acrylic resin. Specimens of both groups, each size 32×10×3 mm, were fabricated. The denture base material was layered with a Gingiva-shade composite resin in thicknesses of 1.0 mm and 1.5 mm, creating subgroups for each material type (n=10). After conditioning of samples, a UTM was used to conduct a 3-point bending test measured the flexural strength and results were analyzed statistically Results: The compression strengths of the injection-molded acrylic resin samples varied between 125.4±3.115 MPa and 114.3±5.074 MPa, whereas the compression strengths of the CAD-CAM prepolymerized acrylic resin varied between 129.4±3.84 MPa and 119.4±8.16 MPa. All test groups maintained flexural strength values above the ISO 20795-1 minimum requirement of 65 MPa, clinical acceptability for denture fabrication. Conclusions: CAD/CAM PMMA denture bases exhibited superior flexural compared to injection-molded, both pre and post aging and in different thickness of GSCR layering.